Ninth European Powder Diffraction Conference - Prague, September 2-5, 2004 (Zeitschrift für Kristallographie / Supplemente, 2006)
Zeitschrift für Kristallographie. Supplement Volume 23 presents the complete Proceedings of all contributions to the IX European Powder Diffraction Conference in Prague 2004: Method Development and Application, Instrumental, Software Development, Materials Supplement Series of Zeitschrift für Kristallographie publishes Proceedings and Abstracts of international conferences on the interdisciplinary field of crystallography.